2017
DOI: 10.1093/molbev/msx082
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenome Diversity in Sardinians: A Genetic Window onto an Island's Past

Abstract: Sardinians are “outliers” in the European genetic landscape and, according to paleogenomic nuclear data, the closest to early European Neolithic farmers. To learn more about their genetic ancestry, we analyzed 3,491 modern and 21 ancient mitogenomes from Sardinia. We observed that 78.4% of modern mitogenomes cluster into 89 haplogroups that most likely arose in situ. For each Sardinian-specific haplogroup (SSH), we also identified the upstream node in the phylogeny, from which non-Sardinian mitogenomes radiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 39 publications
(53 reference statements)
4
69
1
Order By: Relevance
“…Mat. 1E), including a subset ( n = 10) previously reported by O livieri et al (2017). We confirm the observation that ancient Sardinian mtDNA haplotypes belong almost exclusively to macro-haplogroups HV ( n = 16), JT ( n = 17) and U ( n = 9), a composition broadly similar to other European Neolithic populations.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Mat. 1E), including a subset ( n = 10) previously reported by O livieri et al (2017). We confirm the observation that ancient Sardinian mtDNA haplotypes belong almost exclusively to macro-haplogroups HV ( n = 16), JT ( n = 17) and U ( n = 9), a composition broadly similar to other European Neolithic populations.…”
Section: Resultssupporting
confidence: 89%
“…M odi et al (2017) provided the first complete mitogenomes of two Mesolithic individuals and found support for a model in which Mesolithic ancestry on the island was replaced by incoming populations in the Neolithic. O livieri et al (2017), in a companion project to the work described here, analyzed 21 ancient mitogenomes from Sardina as well as 3,491 mitogenomes from contemporary Sardinians and estimated the coalescent times of Sardinian-specific mtDNA haplogroups finding support for most of them originating in the Neolithic or later, but with a few coalescing earlier. Finally, M atisoo -S mith et al (2018) analyzed mitogenomes in a Phoenician colony on Sardinia and found evidence of continuity and exchange between the colony and broader Sardinia.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that, future analyses based on extensive samplings (e.g., ref. [49]), genome-wide genetic markers (e.g., ref. [46]), even together with ancient DNAs (e.g., ref.…”
Section: Discussionmentioning
confidence: 99%
“…[46]), even together with ancient DNAs (e.g., ref. [49]), will provide more details about the admixture history in the Pamirs.…”
Section: Discussionmentioning
confidence: 99%
“…Modi et al 35 sequenced mitogenomes of two Mesolithic individuals and found support for a model of population replacement in the Neolithic. Olivieri et al 36 analyzed 21 ancient mitogenomes from Sardinia and estimated the coalescent times of Sardinianspecific mtDNA haplogroups, finding support for most of them originating in the Neolithic or later, but with a few coalescing earlier. Finally, Matisoo-Smith et al 37 analyzed mitogenomes in a Phoenician settlement on Sardinia and inferred continuity and exchange between the Phoenician population and broader Sardinia.…”
mentioning
confidence: 99%